Sistem Pakar Diagnosa Penyakit Obsessive Compulsive Disorder Hoarding Menggunakan Metode Certainty Factor Berbasis PHP - Rahmaini Hifzah Ruslan; Fithry Tahel (Universitas Methodist Indonesia, 2025)
Obsessive-Compulsive Disorder, or OCD, is a mental health disorder characterized by obsessive thoughts and compulsive actions that are difficult to control. Providing appropriate treatment is crucial to prevent further impact on the quality of life of OCD sufferers. Unfortunately, initial diagnosis is often hampered by time constraints and difficult access to doctors or specialists. Therefore, researchers recommend a PHP-based expert system using the Certainty Factor method. This system mimics the way doctors think when diagnosing OCD, based on symptoms selected by the user. The Certainty Factor is used to calculate the certainty of the diagnosis based on the entered symptoms. The analysis shows that this system is capable of diagnosing with high accuracy, even reaching 100% in some OCD cases. These results demonstrate that expert systems can be a powerful tool for early detection of OCD, allowing for faster and more targeted treatment and care.